Ekonomiska konsekvenser av variation i slaktvikt hos slaktgrisar - Ryssén, Erik; Wåhlin, John (2011)
At present, the Swedish pig industry is in transition. Prices have been low, but feed prices have increased. Therefore, many pig producers have stopped their production. Producers that lack an integrated production may contract piglet’s producers, or may use the mediation services that slaughterhouses provide. This increases uncertainty for these producers and makes it difficult to influence the weight of the pigs. The purpose of this paper is to identify the financial implications of variability in carcass weight within Swedish slaughter pig production. By analyzing the gross margin, with the help of Agriwise calculations, we have been able to detect economic consequences of variability in carcass weight. This paper doesn’t considers factors such as genetics, gender, hierarchy in the population, etc. Already during the first week of production process, this study has found that a low distribution in weight can help to predict the outcome of the slaughter weights. A lower standard deviation at the beginning of the insertion period provides a lower standard deviation when the culling begins. A reduced production period can provide certain economic advantages. However, these advantages can be difficult to achieve. For example, the producers in this study have not been able to increase their gross margin by reducing the production period.